Non-malarial febrile illness: a systematic review of published aetiological studies and case reports from China, 1980–2015 - Ip, DKM; Ng, YY; Tam, YH; Thomas, NV; Dahal, P; Stepniewska, K; Newton, PN; Guérin, PJ; Hopkins, H (BioMed Central, 2024)
Background: Rapid point-of-care tests for malaria are now widely used in many countries to guide the initial clinical management of patients presenting with febrile illness. With China having recently achieved malaria elimination, better understanding regarding the identity and distribution of major non-malarial causes of febrile illnesses is of particular importance to inform evidence-based empirical treatment policy. Methods: A systematic review of published literature was undertaken to characterise the spectrum of pathogens causing non-malaria febrile illness in China (1980–2015). Literature searches were conducted in English and Chinese languages in six databases: Ovid MEDLINE, Global Health, EMBASE, Web of Science™ – Chinese Science Citation Database SM, The China National Knowledge Infrastructure (CNKI), and WanFang Med Online. Selection criteria included reporting on an infection or infections with a confirmed diagnosis, defined as pathogens detected in or cultured from samples from normally sterile sites, or serological evidence of current or past infection. The number of published articles, reporting a given pathogen were presented, rather than incidence or prevalence of infection. Results: A total of 57,181 records from 13 provinces of China where malaria used to be endemic were screened, of which 392 met selection criteria and were included in this review. The review includes 60 (15.3%) records published from 1980 to 2000, 211 (53.8%) from 2001 to 2010 and 121 (30.9%) from 2011 to 2015;. Of the 392 records, 166 (42.3%) were from the eastern region of China, 120 (30.6%) were from the south-west, 102 (26.0%) from south-central, and four (1.0%) were multi-regional studies. Bacterial infections were reported in 154 (39.3%) records, viral infections in 219 (55.9%), parasitic infections in four (1.0%), fungal infections in one (0.3%), and 14 (3.6%) publications reported more than one pathogen group. Participants of all ages were included in 136 (34.7%) studies, only adults in 75 (19.1%), only children in 17 (4.3%), only neonates in two (0.5%) and the age distribution was not specified in 162 (41.3%) records. The most commonly reported bacterial pathogens included Typhoidal Salmonella (n = 30), Orientia/ Rickettsia tsutsugamushi (n = 31), Coxiella burnetii (n = 17), Leptospira spp. (n = 15) and Brucella spp. (n = 15). The most commonly reported viral pathogens included Hantavirus/Hantaan virus (n = 89), dengue virus (DENV) (n = 76 including those with unknown serovars), Japanese encephalitis virus (n = 21), and measles virus (n = 15). The relative lack of data in the western region of the country, as well as in in neonates and children, represented major gaps in the understanding of the aetiology of fever in China. Conclusions: This review presents a landscape of non-malaria pathogens causing febrile illness in China over 36 years as the country progressed toward malaria elimination. These findings can inform guidelines for clinical management of fever cases and infection surveillance and prevention, and highlight the need to standardize operational and reporting protocols for better understanding of fever aetiology in the country.